Road properties of cement-phosphogypsum-red clay under dry and wet cycles. - Yunke Liu; Kaisheng Chen; Hao Jian; Zeyu Liu (PLoS ONE)
In this paper, the road performance and mechanism of cement-phosphogypsum-red clay (CPRC) under dry and wet cycling were systematically investigated using 5% cement as curing agent, the mass ratio of phosphogypsum: red clay = 1:1, and 5% SCA-2 as water stabilizer. The road performance of dry and wet cycle mix was verified with the National Highway G210 Duyun Yangan to Yingshan Highway Reconstruction and Expansion Project as a test road to provide a scientific basis for the application of cement-phosphogypsum-red clay on roads. The results show that the cement-phosphogypsum-red clay unconfined compressive strength decreases with the increase of the number of wet and dry cycles, with a larger decay in the first three times and leveling off thereafter. The CBR value meets the requirements of roadbed fill on highway and Class I roads as stipulated in the Design Code for Highway Roadbeds (JTG D30-2015). SCA-2 water stabilizer reduces the strength of the mixture, but significantly improve the water stability performance of the mixture, the reason SCA-2 water stabilizer active ingredients and mixing particles of physicochemical reaction, the content of ettringite in the mixture is lower than the content of the mixture not mixed with water stabilizers, the generation of quartz, white mica, and kaolinite and other hydrophilic poor material increases, the surface of the cementitious material increases, the seepage channel is reduced, so the strength is reduced, and water stability performance is improved. The roadbed of the test road was smooth and dense, with no scouring, peeling or cracking. The settlement of the roadbed is less than the requirement of "Highway Roadbed Design Specification" (JTGD30-2015). Cement-phosphogypsum-red clay (cement 5%, phosphogypsum 47.5%, red clay 47.5%, SCA-2 water stabilizer 5%) can be used as filler for road bed on highway and primary road base.